How Can Nurse Educators Guide Students by Using ChatGPT as a Teaching Tool? - Karacay, Pelin; Goktas, Polat; Yasar, Ozgen; Kucukkaya, Aycan (Archives of health science and research, 2024)
Cite this article as: Karaçay P, Göktaş P, Yaşar Ö, Küçükkaya A. How can nurse educators guide students by using ChatGPT as a teaching tool? Arch Health Sci Res. 2024;11(3):140-141.